Study of Efficacy Analysis of Intravaginal Misoprostol and Intracervical Dinoprostone in Induction of Labor at a Tertiary Care Hospital in Central India - Hitesh V. Bambhaniya; v, Raj Krishna (Asian Journal of Medical Research, 2019)
Background: Labor induction ranks among the most frequently performed procedures during pregnancy. the present study was conducted for efficacy analysis of intravaginal misoprostol and intracervical dinoprostone in induction of labor. Materials & Methods: A total of 40 women who were admitted to the labor ward beyond thirty-seven weeks of gestation and requiring induction of labor for obstetrical indications were enrolled. Complete demographic and clinical details of all the patients were obtained. All the patients were randomized into two study groups- Intravaginal misoprostol group and intracervical dinoprostone. Bishop scoring was done according to vaginal examination findings and those with Bishop score of six or less were included. Induction was done in both the study groups according to their respective protocols. Duration from time of induction to onset was noted. Need for oxytocin augmentation was recorded separately. All the results were recorded in Microsoft excel sheet and were subjected to statistical analysis using SPSS software. Results: In the comparison of the two medications, the initial Bishop Score did not reveal any significant differences. However, the subsequent Bishop Score, measured 8 hours post-application of the drug, was notably higher in women who received misoprostol for induction. 12.5 percent of the patients of the intravaginal misoprostol group and 32.5 percent of the patients of the intracervical dinoprostone group need oxytocin augmentation. The mean duration of induction and delivery was significantly higher among patients of the intracervical dinoprostone group. Conclusion: Misoprostol has demonstrated superior efficacy in facilitating cervical modifications and in the induction of labor.